Decree-Law of the President of the Arab Republic of Egypt No. 160 of the Year 2013 On Amending Some Provisions of the Traffic Law Promulgated by Law No. 66 of the Year 1973 = قرار رئيس جمهورية مصر العربية بالقانون رقم 160 لسنة 2013 فى شأن تعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.